2017
DOI: 10.1037/str0000017
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of the Mitchell Method Relaxation Technique for the treatment of fibromyalgia symptoms: A three-arm randomized controlled trial.

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Another three studies focused on fighting ailments through Tai Chi and mindfulness [15][16][17][18][19]. Some of the articles carried out more specific therapies, such as the Mitchell method relaxation technique or exposure treatment focused on emotions [20,21]. Below is a table that shows the search strategy used to select the 13 selected articles (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another three studies focused on fighting ailments through Tai Chi and mindfulness [15][16][17][18][19]. Some of the articles carried out more specific therapies, such as the Mitchell method relaxation technique or exposure treatment focused on emotions [20,21]. Below is a table that shows the search strategy used to select the 13 selected articles (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The relaxation technique based on the Mitchell method was effective in reducing pain (42.8%), sleep problems and fatigue (37%). These types of interventions are effective when used as adjuvant treatment, being usually recommended due to the absence of adverse effects in those people who have been diagnosed with fibromyalgia [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Progressive muscle relaxation (PMR) (combined with guided imagery) in cancer patients brought positive results in pain relief [ 100 ]. The Mitchell method—administered for one month—managed to reduce symptoms accompanying fibromyalgia [ 101 ]. An older review of usefulness of relaxation techniques in acute pain management showed however poor performance of these methods [ 102 ].…”
Section: Relaxation Techniquesmentioning
confidence: 99%
“…Within this premise, public interest in the use of complementary and alternative medicine has sharply increased as well. This trend could not fail to attract the attention of scientists from different specialties: physicians, psychologists, researchers, practitioners, and even philosophers who conducted several studies of the data obtained while using ancient East Asian techniques, both for normalizing psychosomatic disorders and for restoring physical condition, having received a vivid confirmation that these methods may effectively function as a healing art for warding off diseases, and enhancing the overall health state of the individual (Amirova, Cropley, & Theadom, 2017;Fuzhong & Harmer, 2014;Reifsteck & Brooks, 2018;West, Liang, & Spinazzola, 2017). Both the Reiki art and other Ancient Oriental self-healing techniques, as well as different recreational activities (various sports, dancing, reading), act as protective internal mechanism, producing a great beneficial effect (Ivanchenko & Zaika, 2017;Kovács, 2018;Rezaei & Khosroshahi, 2018).…”
mentioning
confidence: 99%